Diversity in the medical curriculum: Social dimension analysis script for problem-based learning - Custódio, Lucimara Aparecida Faustino (2021)
This article describes a script for the social dimension’s analysis in the process of Problem Based Learning (PBL) in a medical course. It is a descriptive inventory that was constructed based on existing literature and developed through analyze of 69 paper cases and their respective guides (triggers for the teaching-learning process from first to fourth medical years of a public faculty). Documentary analysis of the qualitative approach was carried out from Discursive Textual Analysis.  The script consisted of axes that characterized the profile of the characters and contexts of the paper cases: identification, space, competence area, health surveillance, living conditions, access to health services, bonding, autonomy and diversities, and vulnerabilities. This article showed how the script itself can guide the construction of problems, and the analysis of the social dimension in health courses whose curricula are mediated by the PBL.